Pragmatic Presupposition in Interpersonal Communication—a Case Study of Lovers’ Dialogue - Chen, Jialiang (Advances in Social Sciences Research Journal, 2021)
Abstract: Pragmatic presupposition is a common linguistic phenomenon in natural language. In real life, an increasing number of people begin to use pragmatic presupposition to carry out interpersonal communication, so as to make the expression richer and more accurate. However, while the appropriate use of pragmatic presupposition is related to the effectiveness of communication, many people cannot attach great importance to the significance of pragmatic presupposition and fail to understand its role in interpersonal communication. This paper takes pragmatic presupposition theory as the theoretical basis and lovers' dialogues as an example to analyze the application of pragmatic presupposition in a specific context with the aim of helping people fully understand pragmatic presupposition theory and promote the effect of interpersonal communication in specific contexts. Key Words: pragmatic presupposition, dialogue, boyfriend and girlfriend, interpersonal communication